Jalaukavacharna (Medicinal Leech Therapy) in Dushta Vrana w. s. r. Diabetic Foot Ulcer - A Case Study - Neha Sharma,; Gaurav Parmar,; Vivek Thakur,; Kulwant Singh Himaliyan,; Anil Dutt, (AYUSHDHARA, 2022)
Ancient Indian medicine has a long and wide history but modern medicine has just recently emerged with focusing on their possible modes of action. Jalaukavacharna or Medicinal Leech Therapy or Hirudotherapy is an old technique of bloodletting and is being widey studied by many researchers for possible effects on numerous diseases as Dushta Vrana Ropana, inflammatory diseases, osteoarthritis, various diseases according to different Doshas etc. Detailed description of the Jalaukavacharna and Jalauka is given in Sushruta Sutra Sthana Thirteen. Researchers have described various properties of leech therapy like anti-inflammatory, analgesics, platelet inhibitory, anticoagulant etc. A 61 years old male patient with history of DMII since 10 years came to RGGPG Ayurvedic College and Hospital, Paprola, Himachal Pradesh with the complaints of wound over left foot with pustular discharge and smell accompanied by fever. After thorough debridement, leech therapy was done for 4 weeks, twice per week followed by once every week for 6 weeks. Strict limb elevation was advised along with strict diabetic management. The treatment followed may be adopted in the future for various cases.